Differentiation of gluteus medius and minimus activity in weight bearing and non-weight bearing exercises by M-mode ultrasound imaging - Dieterich, A.; Petzke, F.; Pickard, Christine; Davey, Paul; Falla, D. (Churchill Livingstone, 2014)
Background: Knowledge on task-specific activity of the deep hip abductor muscles is limited and is required for determining appropriate hip abductor exercises. Objectives: To assess the temporal differentiation of activity of gluteus minimus and the deep and the superficial regions of gluteus medius during weight bearing and non-weight bearing exercises. Design: Repeated measures design on a single recording occasion. Method: M-mode ultrasound was used to capture activity-related muscle motion of the gluteus minimus and medius muscles in 20 healthy volunteers during weight shift, hip hitch, side-lying abduction and active leg lengthening exercises. M-mode traces were computer-processed for detecting muscle motion onsets. Mean onset differences between muscle regions and their intra-individual variability were assessed. Results: In contrast to side-lying abduction, the weight shift and hip hitch exercises resulted in larger onset variability between the gluteus minimus and deep gluteus medius (P < 0.001) and also between the deep and superficial regions of the gluteus medius (P < 0.05). Conclusions: Weight bearing exercises promoted a greater functional differentiation between deep and superficial hip abductor muscles.